‘FRESH OFF THE BOAT’ AND THE MODEL MINORITY STEREOTYPE: A FOUCAULDIAN DISCOURSE ANALYSIS - Hang, Truong Minh; Thanh, Phung Ha (VNU Journal of Foreign Studies; Vol 34 No 5, 2018)
This project studies how the American sitcom Fresh Off the Boat performs the model minority discourse. The performance, in line with the Foucauldian tradition of discourse analysis, is understood based on the networks of events and meanings that have rendered the model minority stereotype intelligible. The study informs that the model minority stereotype entered the discourse on Asian Americans through mainstream media’s rationalization of Asian Americans’ economic success in 1960s, marking a significant change in social perceptions of Asian Americans. It demonstrates that the discursive status of the stereotype has been conditioned by three power networks namely the black-white paradigm, the Asian American family, and the stereotype-based humor in American sitcoms. Fresh Off the Boat , the authors argue , participates effectively in shaping contemporary model minority discourse as it employs the three power networks in an approach more realistic and humane than mere oversimplification of Asian American experience.